Ground-penetrating radar study of the Cena Bog, Latvia: linkage of reflections with peat moisture content - J. Karušs; D. Bērziņš (Bulletin of the Geological Society of Finland, 2015)
Present work illustrates results of the ground-penetrating radar (GPR) study of the Cena Bog, Latvia. Six sub-horizontal reflections that most probably correspond to boundaries between sediments with different electromagnetic properties were identified. One of the reflections corresponds to bog peat mineral bottom interface but the rest are linked to boundaries within the peat body. The radar profiles are incorporated with sediment cores and studies of peat moisture and ash content, and degree of decomposition. Most of the electromagnetic wave reflections are related to changes in peat moisture content. The obtained data show that peat moisture content changes of at least 3 % are required to cause GPR signal reflection. However, there exist reflections that do not correlate with peat moisture content. As a result, authors disagree with a dominant opinion that all reflections in bogs are solely due to changes in volumetric peat moisture content.